A study on hiring process & onboarding practice impacts on employee satisfaction level of a startup company: Best Aid - Shamiha, Maysha (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.